Iron deficiency screening in the first three years of life: A three-decade-long retrospective case study. Issue 4 (June 2014) - Ferrara, M.; Bertocco, F.; Ricciardi, A.; Ferrara, D.; Incarnato, L.; Capozzi, L.
<x content-type="archive" xml:space="preserve">Abstract</x> A three-decade-long retrospective study of iron status in a cohort of 1250 children aged 8–36 months was carried out at the Pediatric Department at the Second University Naples. Iron status was evaluated with independent variables such as family income, weight for height, introduction of cow's milk (CM), iron supplementation and weaning. Iron deficiency (ID) is prevalent in children with low income, early introduction of CM, delayed weaning, over-weight, and in those not receiving iron supplementation (P < 0.05). The first decade (1980–1990) was marked by low family income, while early introduction of CM characterized the first two decades (1980–1990, 1990–2000) (P < 0.05). ID depends on a variety of social and dietary factors. Hematological tests should be performed early to identify children at risk for ID.